Electric transport studies on topological insulators - Xia, Bin (2014)
This thesis presents transport experiments performed on topological insulators systems of Bi2Se3, Ca: Bi2Se3 and Bi1.5Sb0.5Te1.8Se1.2. We first performed the temperature and magnetic dependent measurements of Bi2Se3 and discovered Shubonikov-de Haas oscillations which verify the quality of single crystal. Due to the large bulk conduction contributions, we fabricate Bi1.5Sb0.5Te1.8Se1.2 single crystals whose bulk conductions are strongly suppressed. A “Spin-valve” effect has been observed in the CoFe(5nm)/ Bi1.5Sb0.5Te1.8Se1.2 structure and it may be originated from the interactions between ferromagnetic layer and helical surface states of topological insulator. Moreover, we prepared the nanodevice based on Bi1.5Sb0.5Te1.8Se1.2 nanoflake and observed the two channel conduction mode in the samples. Weak-antilocalization effect and ambipolar field effect were also verified and studied in detail based on the nanodevice by the low temperature electrical transport measurements. Interestingly, the superconducting transition was obtained in the pure Bi2Se3 at the temperature below 4K. We propose that the defects formed during the single crystal growth induce such transitions.